Programmable Automated System for Songbird Ecobehavioral Research (PASSER): Using flexible computer‐integrated feeders to conduct high resolution studies of environment–behavior dynamics in songbirds. Issue 24 (1st December 2018) - Philson, Conner; Ray, Andrew; Foltz, Sarah; Davis, Jason
Abstract: Field studies seeking to identify interactions between the environment and behaviors of wild songbirds are often restricted by time, labor, and accessibility of the site; hampering the collection of long‐term, high‐resolution data. Here, we describe the development, utilization, and initial results of a long‐term field study of wild songbird feeding patterns using data collected through an inexpensive microcomputer‐controlled automated feeder. Our studies indicate the "smart feeder" is capable of reliable and accurate data collection on feeding and behavioral metrics over long durations with relation to a wide range of environmental conditions. This enables detailed analysis of songbird's environment–behavior interactions. Our results have identified trends in environment–behavior interactions, microhabitat variations, species‐specific feeding profiles, and differences in the frequency and involvement of displacement events. Computerized feeders enabled us to address environment–behavior interactions, resulting in more detailed data than traditional observational methods. This reinforces conclusions from previous work regarding the potential for automated data collection to be adapted for a wide variety of research studies across the field of ethology. Abstract : Computer‐automated feeders provide a new way to collect hard‐to‐access data on behavior–environment interactions in songbirds. The PASSER system does just that, enabling a novel way to approach to ecobehavioral questions with a "big data" twist on spatiotemporal environmental variations.